2021
DOI: 10.1556/2006.2021.00083
|View full text |Cite
|
Sign up to set email alerts
|

Fear of missing out (FoMO) and internet use: A comprehensive systematic review and meta-analysis

Abstract: Background and aims FoMO has been considered a predisposing factor toward excessive internet use, and a great deal of literature has investigated the link between FoMO and internet use. However, there is still a lack of cohesion in the literature. Methods The current study have been conducted and reported in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 128 publications
2
14
0
Order By: Relevance
“…It should be noted that this is only a hypothesis, which needs to be tested experimentally and clinically. From the standpoint of concept, people are more likely to fear missing out and tend to get more information about the pandemic due to the uncertainty of the COVID-19 pandemic (58). However, it is almost impossible to obtain all the information about the COVID-9 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that this is only a hypothesis, which needs to be tested experimentally and clinically. From the standpoint of concept, people are more likely to fear missing out and tend to get more information about the pandemic due to the uncertainty of the COVID-19 pandemic (58). However, it is almost impossible to obtain all the information about the COVID-9 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Individual variations in the trait-like characteristic FOMO (Akbari et al, 2021; Elhai et al, 2021) were assessed using the validated FOMOs developed by Przybylski et al, which has a demonstrated high sensitivity and reliability (Przybylski et al 2013). The scale presents 10 items scored on a five-point Likert-type scale ranging from ‘Not at all true of me’ to ‘Extremely true of me’.…”
Section: Methodsmentioning
confidence: 99%
“…Research on FOMO – often conceptualized as a rather stable trait-like characteristic (Wegmann, Oberst, Stodt, & Brand, 2017) – has rocketed in the context of growing concerns about excessive and potentially addictive social media and smartphone use (reviews see e.g. Elhai et al, 2021; Akbari et al, 2021). Accumulating evidence from different lines of research suggests an association between dispositional FOMO and problematic Internet use - in particular in the domains of social media and smartphone use - as well as associated emotional dysregulations and detrimental effects on daily life (Röttinger et al, 2021; Akbari et al, 2021; Rozgonjuk, Sindermann, Elhai, & Montag, 2020; Elhai, Yang, Rozgonjuk, & Montag, 2020; Yuan, Elhai, & Hall, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in Central Europe, dominated by small talks and hollow conversation, marked by nearly obsessive-compulsive avoidance of responsibility and commitment, followed by an era of-mostly completely dispensable-pseudo-organizational communication on smartphone screens: particularly younger people exhibit symptoms of smartphone addiction paired with social isolation (Tateno et al, 2019) alongside nomophobia (Notara et al, 2021), athazagoraphobia, i.e. the fear of being forgotten, and FoMO (Akbari et al, 2021), the fear of missing out. Self-images and self-values are externalized and thus uncontrollable and fragile, while the soul is arid and empty.…”
Section: Social Adjustment and Virtual Networkingmentioning
confidence: 99%